An experimental model of induction of osteoarthritis in New Zealand white rabbit - Abd. Rahim, Nour El Huda; Zulkifly, Ahmad Hafiz; Mohd Jan, Nurul Hafiza; Ibrahim, Mohd Zulfadzli; Amri, Fathonah; Hassan, Habibah; Mohd Zohari, Sarah Haryati; Abu Hassan, Salmah Anim (2021)
Introduction: Historically, animal models for osteoarthritis have been established to facilitate the study of the pathogenesis of osteoarthritis and the potential medical treatment. The anterior cruciate ligament transection (ACTL) and partial meniscal resection model in rabbits have been widely used. The aim of the study was to establish a more effective surgical approach to induce knee osteoarthritis in New Zealand White Rabbits. Materials and Methods: This descriptive study was approved by the Institutional Animal Care and Use Committee (I-ACUC) ethical committee. The surgical approach of induction of osteoarthritis was done in Advanced Orthopedics Research Laboratory, International Islamic University Malaysia. Eight rabbits underwent lateral and medial meniscectomies at bilateral foreleg knees to induce osteoarthritis. The models were examined through physical and radiographic analysis. Results: Physical exams showed that all model animal daily food and water intakes were normal. Animal model knee motion in passive range showed limitation and instability. Radiographic imaging analysis showed osteoarthritic changes in all models. Moreover, no mortality was recorded during the study. The approach requires less surgery time and easier access. The analgesia was more humane and showed faster recovery. Conclusion: These outcomes suggested an effective and feasible technique of inducing knee osteoarthritis in New Zealand White rabbit models.